2006
DOI: 10.1109/tmtt.2006.885993
|View full text |Cite
|
Sign up to set email alerts
|

Study of 2-bit Antenna–Filter–Antenna Elements for Reconfigurable Millimeter-Wave Lens Arrays

Abstract: This paper presents a new reconfigurable antenna-filter-antenna (AFA) element based on slot antennas and switchable resonators. This reconfigurable AFA can operate in four modes of operation as a three-or four-pole filter, and yields a 2-bit variable phase delay. As a result, the multimode AFA can be used as the building block of 2-bit adaptive lens arrays. This paper details design, modeling, and miniaturization of the reconfigurable AFA, and demonstrates its performance through preconfigured prototypes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Consequently, four types of AFA elements can be combined to implement the desired LA phase delay profile with two bits of accuracy. Though the phase relationships are exact only at the center frequency, simulations predict that they remain within 10% of the nominal values for entire passbands of the 3-pole and 4-pole filters [6].…”
Section: B Afa Structuresmentioning
confidence: 86%
See 2 more Smart Citations
“…Consequently, four types of AFA elements can be combined to implement the desired LA phase delay profile with two bits of accuracy. Though the phase relationships are exact only at the center frequency, simulations predict that they remain within 10% of the nominal values for entire passbands of the 3-pole and 4-pole filters [6].…”
Section: B Afa Structuresmentioning
confidence: 86%
“…An incident wave with layer proper polarization is received by the top slot antenna in the input side, passes through a half-wave stripline resonator, and then reradiates from the bottom slot antenna on the output side with orthogonal polarization. The coupling between the slot antennas and stripline resonator takes place at the open ends of the resonator and can be controlled by the length of the portion of the stripline that is exposed to the electric field in the slots and the distance of the coupling region from the center of the slots as well [6]. Fig.…”
Section: A Improved Lens Design Processmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Each AFA module is composed of receive antenna, a nonradiating resonant structure, and a transmit antenna [8][9][10][11][12]. Although the frequency characteristics of the antenna set the limit on the transmission bandwidth of these modules, a more general category of filtering shapes can be synthesized using this method.…”
Section: Antenna-filter-antenna Conceptmentioning
confidence: 99%
“…Previously, it had also been reported that beam scanning can be realized by adding active component to each element of a transmitarray. [11][12][13][14][15] However, all the aforementioned approaches were reported to manipulate the electromagnetic (EM) waves through the gradient phase accumulation along a relatively long path in natural material or metamaterial. Several techniques have been adopted by different groups to effectively reduce the thickness of transmitarrays, such as by using large refractive-index materials.…”
mentioning
confidence: 99%